Leadership emergence and team psychological cohesion cultivation mechanism in English Project-Based Learning from the perspective of group dynamic - Shixuan Chang (Environment and Social Psychology, 2025)
Based on group dynamics theory, this study employs a mixed-methods approach to explore the cultivation mechanisms and interactive relationships between leadership emergence and team psychological cohesion in English project-based learning (PBL). The research selected 160 tenth-grade students from a provincial model senior high school, with the experimental group engaging in a 12-week English PBL program. Data were collected through questionnaire surveys, classroom observations, social network analysis, and in-depth interviews. The findings reveal that: (1) Leadership emergence exhibits three-stage characteristics—exploration, differentiation, and integration phases. Individual factors such as English proficiency and personality traits, along with contextual factors including task complexity and group size, jointly influence leadership development, with 65% of teams forming distributed leadership structures. (2) Team cohesion demonstrates a four-dimensional structure encompassing task, social, learning, and emotional dimensions. The experimental group showed significantly higher cohesion than the control group (4.20 vs. 3.33), with clarity of shared goals, collective efficacy, and group norms identified as key influencing factors. (3) A bidirectional interactive relationship exists between leadership and cohesion, with leadership exerting a total effect of 0.72 on cohesion and cohesion demonstrating a reciprocal effect of 0.55 on leadership, forming a positive spiral. (4) Project activities such as collaborative tasks, cross-cultural themes, multimodal presentations, and reflective dialogues exhibit differentiated effects on cohesion cultivation. This study unveils the unique group dynamics mechanism in English PBL, providing theoretical foundations and practical guidance for optimizing instructional design and promoting students' core competencies development.